Interleukin-8 -251A/T gene polymorphism and lung cancer susceptibility: a meta-analysis - Wang, Xiao-Bin (J Cell Mol Med, 2015)
Many studies have examined the association between the interleukin-8 -251T/A (rs4073) gene polymorphism and lung cancer risk in various populations, but the results have been inconsistent. In this meta-analysis, PubMed was searched for case–control studies published through 01 December 2013. The data were extracted, and pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated. We assessed six published studies on the association between the interleukin-8 -251T/A polymorphism and lung cancer risk. The included studies yielded a total of 3265 lung cancer cases and 3607 controls. For the homozygous A/A and A allele carriers (T/A + A/A), the pooled ORs for all studies combining 3265 cases and 3607 controls were 1.03 (95% CI = 0.92–1.14; P = 0.235 for heterogeneity) and 1.07 (95% CI = 0.96–1.19; P = 0.245 for heterogeneity) when compared with the homozygous wild-type genotype (T/T). When the analysis was stratified by ethnicity, significant risks were found among Asians for both the A allele carriers and the homozygous A/A individuals. However, no significant associations were found in non-Asian populations using any of the genetic models. This meta-analysis suggests that the interleukin-8 -251A allele confer an increased risk for the development of lung cancer among Asians.